Looking on Indigo Flycatcher (Eumyas indigo) Hunting Behaviour: Time, Ecology, and Habitat Preference - Agung Sih Kurnianto; Arief Sugiharto; Nia Kurniawan (Journal of Tropical Life Science, 2020)
Hunting is the main support of life for the insectivores bird of the world. Through an understanding of Indigo Flycatcher behavior character, we compiled new information for the daily behavior of Indigo Flycatcher and Muscicapidae family in general. The study was conducted at 3 periods to interpret the effect of different seasons conditions: the first period (rainy season, 1 – 30 January 2015), the second period (dry season, 1-30 June 2015), the third period (transition season, 1 – 30 November 2015). The research station covers 3 research points (A=edge of the forest, b = garbage dump, c = dense forest. A canonical correspondence (CCA) was used to understand the significance of the interaction between the abiotic factors and season. Based on the observations, the transition of the season became the most preferred moment for Indigo Flycatcher. Indigo flycatcher hunts in a group, both singular and mixed. Point B is the most common location of Indigo Flycatcher hunting activity.